"Truthiness" and Second-Level Agenda Setting: Satire News and Its Influence on Perceptions of Television News Credibility. (June 2015) - Littau, Jeremy; Stewart, Daxton R. "Chip"
This study examined the impact of satire news programs on perceptions of media credibility. Using second-level agenda setting as a theoretical framework, the results of this mixed-methods study show that negative portrayals of television news on these satire news shows make salient certain negative attributes that match viewers' perceptions of credibility. A survey ( N = 650) found that Daily Show / Colbert Report viewers had less positive views about the credibility of television news programs, while content analysis ( N = 401) of 4 weeks of episodes of The Daily Show and The Colbert Report reflected the results of the survey, showing that television news programs, particularly those on cable, were more frequently portrayed negatively and made the target of jokes. The analysis shows television news is a frequent target of these satire shows' criticisms and these shows' negative attributes are made salient, which is reflected in the survey respondents' low credibility scores for this medium.